Implementation Of The Family Planning Program In The Work Area Of Puskesmas Rawat Inap Karya Wanita, Rumbai District, Pekanbaru City: Implementasi Program Keluarga Berencana Di Wilayah Kerja Puskesmas Rawat Inap Karya Wanita Kecamatan Rumbai Kota Pekanbaru - Wisye Sita Agtria; Ahmad Hanafi; Reno Renaldi; Yanwir Kamal; M.Dedi Widodo (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Family planning is an effort to regulate the birth of children, the ideal age range for giving birth, and to regulate pregnancy through the promotion of protection and assistance in accordance with reproductive rights to create a quality family and realize the norms of a happy and prosperous small family. The Karya Wanita Inpatient Community Health Center, Rumbai Subdistrict, Pekanbaru City is an area with the lowest active family planning coverage rate of 34.4%. Problems found in The Community Health Center for Inpatient Karya Wanita for the Family Planning Program is still inadequate in terms of Human Resources, Facilities and Infrastructure and the distribution of information is still uneven. The purpose of this study was to determine the implementation of the Family Planning Program at the Karya Wanita Community Health Center, Rumbai District, Pekanbaru City in 2022. This type of research is a qualitative research and descriptive research method to 6 informants consisting of the head of the community health center, the holder of the maternal and child health/family planning program, the midwife and 3 family planning acceptors. This research was carried out in April 2022 at the Karya Wanita Inpatient Community Health Center, Rumbai District, Pekanbaru City. Data was collected by means of in-depth interviews related to family planning programs at community health centers, document searches, and observations The results of this study indicate that there is still a lack of human resources in the community health center and in the family planning program and the incomplete facilities and infrastructure as well as the lack of distribution of counseling carried out by the community health center which can hinder the implementation of the program in the community health center. Suggestions from this study are the need for additional health workers in the family planning program, complete facilities and infrastructure, and increase counseling about family planning programs that are scheduled and evenly distributed. Keluarga Berencana (KB) adalah upaya mengatur kelahiran anak, jarak usia ideal melahirkan, dan mengatur kehamilan melalui promosi perlindungan dan bantuan sesuai hak reproduksi untuk mewujudkan keluarga berkualitas serta mewujudkan norma keluarga kecil bahagia dan sejahtera. Puskesmas Rawat Inap Karya Wanita kecamatan Rumbai Kota Pekanbaru merupakan wilayah dengan angka cakupan KB aktif terendah yaitu sebesar 34,4%. Permasalahan yang ditemukan di Puskesmas Rawat Inap Karya Wanita untuk Program Keluarga Berencana ialah masih kurang memadai nya Sumber Daya Manusia, Sarana dan Prasarana serta penyuluhan yang masih kurang merata. Tujuan penelitian ini ialah untuk mengetahui pelaksanaan Program Keluarga Berencana di Puskesmas Karya Wanita Kecamatan Rumbai Kota Pekanbaru Tahun 2022. Jenis penelitian ini ialah penelitian kualitatif dan metode penelitian deskriptif kepada 6 orang informan terdiri dari Kepala puskesmas, Pemegang Program KIA/KB, Bidan dan 3 Akseptor KB. Penelitian ini telah dilaksanakan pada bulan April 2022 di Puskesmas Rawat Inap Karya Wanita Kecamatan Rumbai Kota Pekanbaru. Pengumpulan data dilakukan dengan cara wawancara mendalam berkaitan dengan program keluarga berencana di puskesmas, penelusuran dokumen, dan observasi. Hasil penelitian ini menunjukkan masih kurangnya Sumber Daya Manusia di puskesmas serta dalam program Keluarga Berencana dan masih belum lengkapnya tersedianya sarana dan prasarana serta masih kurang merata penyuluhan yang dilakukan oleh pihak puskesmas yang dapat menghambat pelaksanaan program di dalam puskesmas. Saran dari penelitian ini adalah perlunya penambahan Tenaga Kesehatan di dalam Program Keluarga Berencana, melengkapi sarana dan prasarana, dan meningkatkan penyuluhan tentang program KB yang terjadwal dan merata.